Mediated Tarekat Qadiriyah wa Naqshabandiyah in the Digital Era: An Ethnographic Overview - Zulfan Taufik; Muhammad Taufik (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
This article examines how Tarekat Qadiriyah wa Naqshabandiyah (TQN) utilizes online media to strengthen its existence. As an integral part of the Islamic revival in Indonesia, Sufi orders (tarekat) are facing remarkable challenges and opportunities in maintaining their existence in the digital era. Nevertheless, previous studies observed Sufi orders as a traditional community that would be exterminated by the pace of modernization and globalization. This article argues that Sufi orders may survive in the internet of things era, contrary to preceding discourses. Based on ethnography research, both online and offline, the authors found out that the vitality of the Sufi order can adapt, develop, and innovate using online media. TQN's use of online media through various platforms proves Sufi order’s adaptive efforts to the internet-based era. TQN’s online media provide informations on Islamic  and Sufism teachings, news, schedule of activities, and fundraising. Even though TQN members’ being active in cyber-Islamic environments, they resist online asceticism thus leverage the vertical-personal obedience, conservative authorities, and sacred rituals. These practices done by TQN members illuminate its identity as an authentic online sufism. Premises shown in this paper may enrich the scope of study within the relationship of Sufi orders and Islamic-cyber environment, especially in Indonesian context.